Randomized trial comparing luteinizing hormone supplementation timing strategies in older women undergoing ovarian stimulation. Issue 3 (September 2015) - Behre, Hermann M.; Howles, Colin M.; Longobardi, Salvatore; ,
Abstract: In this open-label study, women aged 36–40 years undergoing ovarian stimulation were randomized to recombinant human FSH (rhFSH) plus recombinant human luteinizing hormone (rhLH) from stimulation day 1 (group A; n = 103), or rhFSH alone (days 1–5) followed by rhFSH plus rhLH from day 6 (group B; n = 99). The primary objective was equivalence in number of oocytes retrieved per patient. The mean (±SD) number of oocytes retrieved was 9.7 (±6.9) in group A and 10.9 (±6.5) in group B; the estimated difference between groups (−1.28 oocytes [95% confidence interval: −3.15 to 0.59]) did not reach the predefined limit of equivalence (±3 oocytes). The study's primary objective was therefore not met. In both groups, a mean (±SD) of 1.9 (±0.6) embryos were transferred per patient. Implantation rates were 24.7% in group A and 13.3% in group B. Clinical pregnancy rates per started cycle and per embryo transfer were 31.6% and 34.4% in Group A, 17.2% and 18.9% in Group B. Ovarian hyperstimulation syndrome was reported in four (group A) and five (group B) patients. The potential benefit of initiating LH supplementation earlier during ovarian stimulation in older women is of interest, warranting further exploration.